Pengendali Lampu dan Pintu Dengan Perintah Suara Berbasis Android dan Arduino Uno - Yodhi Yuniarthe; Romi Hendri; Yonaldo Anggara (Universitas Mitra Indonesia, 2021)
AbstractCurrently, Android smartphones are widely used in various fields, not only as a means of communication, but nowadays smartphones can control home appliances because the development of Android operating features is increasingly sophisticated. One of the speech recognition technologies is one of the technological breakthroughs that are currently widely used compared to Bluetooth technology. Speech recognition operation by simply saying a command becomes more practical and efficient. Therefore the authors propose speech recognition or voice via an Android smartphone as a device that can be operated in controlling lights with an input system or controller in the form of a voice. This study aims to make applications to make it easier in everyday life more practical, especially in everyday mobility, so that the light control device and house doors with sound can help the limited mobility of users.